Wintering, grazing, and fattening steer calves. 1.) The value of trace minerals in a wintering and fattening ration. 2.) Self feeding grain in drylot vs. self-feeding on bluestem pasture - Smith, E.F.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Chemical analysis of the feeds commonly fed in this area has revealed no deficiency in the trace minerals, copper, cobalt, iron, manganese, and iodine, in view of what we know of the requirements of cattle for these minerals. It is possible that for some reason the minera1s present are not available to the animal in sufficient quantity and perhaps not in the proper ratio. One of the objectives of this test is to determine the effect of introducing; trace minerals at a commonly used level into standard Kansas wintering and fattening rations. Another phase of the test is to compare self-feeding grain in drylot to self-feeding grain on grass for calves handled in the deferred full-feeding program. The system of deferred full-feeding, using good quality steer calves, consists of three phases: (1) producing 225-250 pounds of gain during the winter; (2) grazing 90 days without grain; (3) full-feeding 100 days in the drylot.
Keywords: Beef; Trace minerals; Drylot vs. self-feeding; Bluestem pasture